The brain is kind of a big deal - Seluk, Nick (2019)
Have you ever thought about everything your brain does for you? It is always working to keep you alive and safe. (Plus it lets you think about funny stuff, too.) So why is the brain such a big deal? Because it makes you YOU, of course!
Includes glossary
6-10
Keywords: Brain -- Juvenile literature; Nonfiction; Picture books